Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1371/journal.pone.0099633
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear NF-κB p65 in Peripheral Blood Mononuclear Cells Correlates with Urinary MCP-1, RANTES and the Severity of Type 2 Diabetic Nephropathy

Abstract: AimsTo investigate if nuclear NF-κB p65 expression in ex vivo isolated peripheral blood mononuclear cells correlates with urinary MCP-1 or RANTES and the severity of type 2 diabetic nephropathy.MethodsAccording to their urinary albumin-to-creatinine ratio (uACR), 107 patients with type 2 diabetes (eGFR >60 ml/min) were divided into normal albuminuria group (DN0 group, 38 cases), microalbuminuria group (DN1 group, 38 cases), and macroalbuminuria group (DN2 group, 31 cases), compared with matched healthy normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 19 publications
2
27
0
Order By: Relevance
“…The present study showed that the DM group had increased protein and mRNA levels of NF-κB p65 and its active form phospho-NF-κB p65. The result was consistent with previous studies, which found increased NF-κB activity in diabetic animals (5,7,30). IκBα is an inhibitor of the activation of NF-κB p65, which can suppress the phosphorylation of NF-κB p65.…”
Section: Discussionsupporting
confidence: 93%
“…The present study showed that the DM group had increased protein and mRNA levels of NF-κB p65 and its active form phospho-NF-κB p65. The result was consistent with previous studies, which found increased NF-κB activity in diabetic animals (5,7,30). IκBα is an inhibitor of the activation of NF-κB p65, which can suppress the phosphorylation of NF-κB p65.…”
Section: Discussionsupporting
confidence: 93%
“…MCP-1 is the strongest chemotactic factor for monocytes and urinary MCP-1 secretion levels are upregulated in multiple renal diseases, including DN (23,24). MCP-1 has an important role in the pathogenesis of glomerular and progressive tubulointerstitial lesions via monocyte recruitment and activation (23).…”
Section: Discussionmentioning
confidence: 99%
“…MCP-1 has an important role in the pathogenesis of glomerular and progressive tubulointerstitial lesions via monocyte recruitment and activation (23). Increased urinary excretion of MCP-1 in patients with established DN (patients with micro-or macro albuminuria) is likely due to the enhanced production of MCP-1 in the renal tubules, which is presumably induced by excessive exposure to plasma protein filtered from the damaged glomeruli.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and experimental evidence implicates NF-κB activation and regulated genes in the early phases, progression and final complications of diabetes and, as such, its inhibition offers therapeutic intervention opportunities [11][12][13][14][15][16][17]. Although several NF-κB inhibitors have reached phase II/III clinical trials for inflammatory diseases [18,19], most research into cardiovascular or renal diseases is only in the preliminary experimental phase [20].…”
Section: Introductionmentioning
confidence: 99%